Aural Rehabilitation through Music Workshops for Cochlear Implant Users - van Besouw, Rachel M.; Nicholls, David R.; Oliver, Benjamin R.; Hodkinson, Sarah M.; Grasmeder, Mary L. (Journal of the American Academy of Audiology, 2014)
Background: It has been reported that after speech perception, music appreciation is the second most commonly expressed requirement among cochlear implant (CI) recipients. Certain features of music are known to be more readily accessible; however, provision of music rehabilitation for adult CI users is limited.Purpose: A series of music workshops were organized to (1) enable attendees to explore which aspects of music they are able to perceive and appreciate; (2) raise awareness of listening strategies, technology, and rehabilitation resources for music; and (3) develop ideas, and prototype software, for inclusion in a music rehabilitation program. The therapeutic value of music workshops was concurrently investigated.Research Design: A qualitative, longitudinal study was used. Two consultation meetings were held before a series of nine music workshops that occurred over a period of 5 mo.Study Sample: Five adult CI users participated in consultations before the workshops. Twenty-eight adult CI users from the South of England Cochlear Implant Centre attended at least one of the workshops.Intervention: Participants could attend as many workshops as they wished. Each workshop lasted between 2 to 2.5 hr and included individual computer-based and group activities.Data Collection and Analysis: Responses to open-ended questions were transcribed in the consultation meetings and used to develop workshop activities. A preworkshop survey was used to determine attendees’ aspirations and expectations. Postworkshop surveys were used to qualitatively and quantitatively evaluate attendees’ immediate reactions to the workshop content, software, and perceived benefits. A 2-month, postworkshop survey evaluated the longer-term impact of the workshops.Results: Overall reaction to the workshops and prototype software was positive. All attendees indicated that they anticipated changing how they engaged with music as a result of the workshops, and data from the preworkshop and postworkshop surveys suggest a positive change in listening habits.Conclusions: The workshops proved to be an effective means of simultaneously encouraging music exploration in a social and safe environment and obtaining feedback on prototype rehabilitation materials. Survey data suggested that through group listening and practical activities, certain aspects of music can be accessible and rewarding through a CI, leading to positive changes in attitude and behavior toward music.
Keywords: Cochlear implants; music; therapy; training; rehabilitation; workshops; evaluation